PEMBERIAN KOTORAN SAPI SEBAGAI PUPUK KANDANG TERHADAP PRODUKSI AWAL RUMPUT RAJA (Pennisetum purpuphoides) - Marna Eoh; Lea Marlyn Rehatta (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This study aimed to examine the effect of cattle manure application on the early production of king grass (Pennisetum purpureophoides). The experiment was conducted using a Completely Randomized Design (CRD) consisting of two treatment levels, namely P0 (control, without manure application) and P1 (cattle manure application), with each treatment replicated four times. The variables observed in this study included the number of shoots, leaf length, leaf width, and plant height. The results indicated that the number of shoots during the early growth phase of king grass showed no significant difference between treatments from the first to the third week; however, in the fourth week, treatment P1 exhibited a significant difference compared to P0. Leaf length showed differences between treatments from the first week of observation, where P1 consistently produced longer leaves than P0. Leaf width also demonstrated significant differences between treatments throughout weeks one to four, with P1 consistently outperforming P0. Regarding plant height, P1 showed a significant difference compared to P0 during the first and second weeks of observation. Overall, the application of cattle manure significantly enhanced the early production of king grass, with the optimal dose obtained under treatment P1, which yielded the best growth performance.